Compliance Risk Management : Developing Compliance Improvement Plans - Brondolo, John (Technical Notes and Manuals; Technical Notes and Manuals ;, 2022)
All tax administrations seek to maximize the overall level of compliance with tax laws. Compliance improvement plans (CIPs) are a valuable tool for increasing taxpayers' compliance and boosting tax revenue. This note is intended to help tax administrations develop a CIP, by providing guidance on the following issues: (1) how to identify and rate compliance risks; (2) how to treat risks to achieve the best possible outcome; and (3) how to measure the impacts that treatments have had on compliance outcomes.